Moringa Oleifera in Malnutrition: A Comprehensive Review - Mushtaq, Bilal S.; Hussain, Muhammad Bilal; Omer, Rabia; Toor, Hafiz Ahmad; Waheed, Marwa; Shariati, Mohammad Ali; Sergey, Plygun; Heydari, Mojtaba (Current Drug Discovery Technologies, 2021)
Nutritional deficiency is a major concern in developing countries, resulting in serious health consequences like mental and physical growth retardation. Moringa oleifera (Moringa), a nutritious plant growing in tropical regions of developing countries, is a candidate for overcoming nutritional deficiency. Moringa leaves are rich in protein including sulphur containing amino acids. It contains high amounts of vitamin C than oranges, a higher concentration of vitamin A than carrots, higher calcium content than milk and more potassium than bananas. Moreover, there is 9 times more iron in moringa than spinach and 4 times more fiber than oats. This review enlightens and explores the nutritional diversification of Moringa oleifera and other benefits which make it a better choice to use in our daily diet to combat malnutrition.
Keywords: traditional medicine